2018
DOI: 10.1007/s10616-018-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived polysaccharides activate dendritic cell-based anti-cancer immunity

Abstract: Today, cancers pose a major public health burden. Although a myriad of cancer treatments are available, only a few have achieved clinical efficacy. This is partly attributed to cancers capability to evade host immunity by converting dendritic cells (DCs) from potent stimulators to negative modulators of immunity. Dendritic cell-based immunotherapy attempts to resolve this problem by manipulating the functional characteristics of DCs. Plant-derived polysaccharides (PDPs) can stimulate the maturation of DCs conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…A large amount of experimental and clinical evidence indicates that long-term inflammation can increase the risk of cancer because a variety of inflammatory mediators can directly regulate the expression of oncogenes. In addition, key inflammation-related enzymes such as iNOS and COX-2 are associated with cancer induced by long-term inflammation (86, 87). Therefore, it is important to continue studying whether the pro- and anti-inflammatory factors induced by plant polysaccharides can maintain equilibrium in the body without causing harm due to excessive activation.…”
Section: Perspectivementioning
confidence: 99%
“…A large amount of experimental and clinical evidence indicates that long-term inflammation can increase the risk of cancer because a variety of inflammatory mediators can directly regulate the expression of oncogenes. In addition, key inflammation-related enzymes such as iNOS and COX-2 are associated with cancer induced by long-term inflammation (86, 87). Therefore, it is important to continue studying whether the pro- and anti-inflammatory factors induced by plant polysaccharides can maintain equilibrium in the body without causing harm due to excessive activation.…”
Section: Perspectivementioning
confidence: 99%
“…Various plant-derived polysaccharides have been isolated and shown immunostimulatory activity (Kikete et al, 2018). Here, we found that GUPS promoted the maturation of DCs through TLR4 and its downstream p38, JNK and NF-κB signaling pathways, increased IL-12 production in vivo and enhanced the immunity of immunosuppressive mice.…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that polysaccharides can stimulate immune cells through different types of receptors including TLRs and scavenger receptors, which sequentially activate MAPK and NF-κB signaling pathways (Ferreira et al, 2015;Kikete et al, 2018). Our previous studies showed that Pleurotus ferulae polysaccharides and G. uralensis water extract promoted DCs maturation and cytokine production through TLR4 signaling pathway (Aipire et al, 2017;Li et al, 2017a;Li et al, 2017b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Polysaccharides, which are macromolecules composed of long chains of monosaccharide units, are the key bioactive components of TCMs, and they possess immunomodulatory, antitumor, anti-in ammatory, hypoglycemic, anti-aging, and antioxidant effects [34][35][36][37]. In our previous study, the polysaccharide KSWP was isolated from Kochia scoparia fruit.…”
Section: Discussionmentioning
confidence: 99%